2019
DOI: 10.5797/jnet.oa.2018-0134
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Treatment Results of In-hospital Acute Ischemic Stroke due to Large Vessel Occlusion Treated by Mechanical Thrombectomy

Abstract: The purpose of this study was to investigate the characteristics, time-line, and treatment results of in-hospital acute ischemic stroke due to large vessel occlusion (LVO) treated by mechanical thrombectomy. Methods: The authors investigated 10 patients (six males and four females; mean age 78.6 years, range 65-92) with in-hospital LVO treated by thrombectomy between January 2016 and July 2018 in our institute. Patient characteristics, procedural results, clinical outcome, and time-line data of thrombectomy (l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…Previous studies have reported high mortality and low rates of discharge to home following thrombectomy for patients who develop LVO in-hospital compared to those who develop it in the community. 2,[4][5][6] In this series, the rates of both mRS 5-6 and mRS 0-2 at discharge were a little higher in the own hospital-onset patients than in the other two groups. As mentioned earlier, the increased interest and understanding of emergency stroke management may have helped improve the outcomes of patients who develop in-hospital LVO, especially in comprehensive stroke centers or thrombectomy-capable stroke centers.…”
Section: Procedural and Clinical Outcomes Of Mechanical Thrombectomymentioning
confidence: 47%
See 1 more Smart Citation
“…Previous studies have reported high mortality and low rates of discharge to home following thrombectomy for patients who develop LVO in-hospital compared to those who develop it in the community. 2,[4][5][6] In this series, the rates of both mRS 5-6 and mRS 0-2 at discharge were a little higher in the own hospital-onset patients than in the other two groups. As mentioned earlier, the increased interest and understanding of emergency stroke management may have helped improve the outcomes of patients who develop in-hospital LVO, especially in comprehensive stroke centers or thrombectomy-capable stroke centers.…”
Section: Procedural and Clinical Outcomes Of Mechanical Thrombectomymentioning
confidence: 47%
“…Acute stroke due to LVO commonly arises in patients in the community, but LVO can also develop at medical facilities during hospitalization. [2][3][4][5][6] Mechanical Neurologia medico-chirurgica Advance Publication Date: March 5, 2020 hospital that does not provide thrombectomy, additional time is required for the inter-hospital transfer.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical thrombectomy has also been established as a safe procedure for patients with IHOS in terms of sICH and other procedure-related complications, even in critically ill patients with a higher antithrombotic therapy burden [ 1 , 3 , 18 ]. Several studies have reported that the incidence of periprocedural complications was not significantly higher in IHOS patients compared to patients with COS, and the occurrence of sICHs was evenly distributed between the two groups [ 1 - 5 , 18 - 20 ]. Our meta-analysis also verified these results.…”
Section: Discussionmentioning
confidence: 99%
“…While randomized clinical trials have investigated the impact of mechanical thrombectomy on the outcomes of patients with acute ischemic stroke, these studies have primarily focused on patients who present to the emergency department from the community setting and follow specific treatment pathways for stroke. However, a notable proportion of all strokes occur in hospitalized patients, who may not be included in specific protocols for acute ischemic stroke management [ 3 , 5 ]. Moreover, these patients differ from the general population because they carry concurrent acute medical conditions requiring a hospital stay and are more often ineligible to receive intravenous thrombolysis [ 3 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, similar results were also reported. 5 , 6) This is because arrhythmia, including atrial fibrillation, ischemic heart disease, and heart failure, which cause cardiogenic cerebral infarction, are treated in the cardiology department. Furthermore, stroke onset was reported in approximately 1% of inpatients with myocardial infarction.…”
Section: Discussionmentioning
confidence: 99%